Ullrich–Turner Syndrome and Tumor Risk: Is There Another Chance to Early Gonadectomy in Positive TSPY and SRY Patients? - Silveri, Massimiliano; Grossi, Armando; Bassani, Francesca; Orazi, Cinzia; Camassei, Francesca Diomedi; Zaccara, Antonio (European Journal of Pediatric Surgery, 2016)
The presence of the Y chromosome in the karyotype of patients with disorders of sex differentiation is significantly associated with an increased risk to develop specific types of malignancies, predominantly type II germ cell tumors (GCTs). Gonadoblastoma in the gonads without an obvious testicular differentiation and intratubular germ cell neoplasia of unclassified type in testicular tissue are the precursor lesions of most GCTs. Gonadal dysgenesis, the characteristic feature of Ullrich–Turner syndrome (UTS), further contributes to increase this tumor risk. The reported incidence of Y chromosome material in UTS is 6 to 8% and in these cases an early gonadectomy is strongly recommended to prevent the risk of a malignancy. The aim of this work was to retrospectively analyze the clinical outcome and the histopathological and cytogenetic findings of our UTS patients who underwent gonadectomy to establish strict selection criteria aimed at promoting an organ-sparing surgery.
Keywords: Ullrich–Turner syndrome; gonadal stromal tumors; gonadoblastoma; mosaicism; gonadectomy